Nienależyte sprawowanie opieki. Odpowiedzialność odszkodowawcza opiekuna - Głowacka, Aleksandra (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Title III of The Family and Guardianship Code, section I and II, which refer to guardianship and curatorship, do not create directly regime of liability which would be applied in case of improper performance of guardian duties connected with exercising guardianship over a person and their property. However, wording of the article 164, according to which claim of a person under the guardianship for the compensation of loss incurred as a result of improper performance of guardian duties, shall be barred after three years from cessation of a guardianship or exemption from exercising guardianship duties, allows to accept that the legislator has foreseen such kind of liability, although provision of article 164 considers only the limitation period of claims of a person under the guardianship. The present study exhibits views of doctrine and jurisprudence within the area of compensatory liability of the guardian and the framework of due diligence they should demonstrate when exercising guardian duties. Eventually, the issue of judicial supervision of exercising the guardianship has been discussed.
Keywords: opieka nad dzieckiem; opieka rodzicielska; opiekun; nienależyta staranność; odpowiedzialność odszkodowawcza